Addressing power imbalances in global health: Pre-Publication Support Services (PREPSS) for authors in low-income and middle-income countries. Issue 2 (23rd February 2020) - Busse, Clara; August, Ella
Abstract : The contextual knowledge and local expertise that researchers from low-income and middle-income countries (LMICs) contribute to studies in these settings enrich the research process and subsequent publications. However, health researchers from LMICs are under-represented in the scientific literature. Distally, power imbalances between LMICs and high-income countries, which provide funding and set priorities for research in LMICs, create structural inequities that inhibit these authors from publishing. More proximally, researchers from LMICs often lack formal training in research project management and in publishing peer-reviewed research. Though academic journals may value research from LMICs conducted by local researchers, they have limited time and financial resources to support writing, causing them to reject manuscripts with promising results if they lack development. Pre-Publication Support Service (PREPSS) is a non-profit, non-governmental organisation that works to meet this need. PREPSS provides onsite training, peer-review and copy editing services to researchers in LMICs who wish to publish their health research in peer-reviewed journals. Authors are not charged for these services. After receiving PREPSS services, authors submit their manuscript to a peer-reviewed journal. The PREPSS model is one of many interventions necessary to restructure global health research to better support health researchers in LMICs and reduce current power imbalances.